Managing Precarity: Understanding Latinas' Sexual and Reproductive Care-Seeking in a Midwest Emergent Latino Community. (April 2021) - Guerra-Reyes, Lucia; Palacios, Iris; Ferstead, Amanda
In this qualitative interview study, we took a two-pronged approach to understand the complexities of sexual and reproductive health (SRH) care access for Latinas in an emerging Latino community (ELC). Phase 1 assessed the SRH resources available for uninsured Latinas through provider interviews. In Phase 2, we interviewed 15 Latina-identified women about their considerations for SRH care-seeking. The scant options for SRH care are focused largely on contraception and pregnancy. Providers viewed themselves as prevention-oriented and perceived Latinas did not prioritize preventive care. Women described compounding challenges and precarious conditions. Annual checkups, accessing contraception, and treating vaginal infections were identified as needs. Barriers to SRH care were enhanced in an ELC. Participants described too much paperwork and limited time as organizational barriers which aggravated others, such as language limitations and feeling embarrassed to ask questions. Further research on SRH care using a reproductive justice approach is needed in ELCs.